WIND CHARACTERISTICS ANALYSIS IN FOUR POTENTIAL TOWNSHIPS IN MYANMAR (ASEAN Engineering Journal, 2022)
Myanmar has set renewable energy aspirations in the energy mix of the country to meet growing energy demand and to increase clean access to electricity as indicated in Myanmar’s Intended Nationally Determined Contribution. Among renewable energy resources, solar and wind energy are expected to contribute to 9% of total energy mix. Although there have been initiatives on the implementation of solar photovoltaic in Myanmar, implementation of wind energy has not been reported. Few studies on wind energy in Myanmar focused on resource assessment investigating the spatial variation of wind speed and power density. Little has been studied on the seasonal nature and persistence of wind in Myanmar from the perspective of energy generation. This study aims at generating wind speed and power density maps of Myanmar using most recent wind data from 2010 to 2017 to identify potential townships with favourable wind conditions. Prominent wind direction, seasonal variations and wind speed persistence were analyzed for four townships with favourable wind conditions. Weibull parameters suggest that frequency of wind is also favourable for wind energy generation. Hence, this study has identified Chauk, Kyaukpadaung, Meiktila and Natogyi townships as potential regions for wind energy development with estimated power producing time of 53.17% and 65.91% of a year at average wind speed of 4 m/s above. This study serves as a basis for further resource assessment for micrositing of wind turbines to identify feasible sites for wind energy generation in Myanmar.